Analyse economique de la culture en couloirs a composante fourragere - Sumberg, J.E.; McIntire, John M.; Okali, C.; Atta-Krah, A.N. (1987)
Evaluates alley farming models with small ruminants based on field and experimental data from southwest Nigeria, and compares them to basic alley cropping and to fallow systems. Describes the basic fallow model, the basic alley cropping model without animals, the alley farming model with goats, as well as with sheep.